The Representation of Gender in a Textbook Entitled When English Rings a Bell - Fenty Lidya Siregar; Henni Henni; Silvanni Comara (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. Despite countless criticism that English textbooks contain gender biases, teachers still use textbooks in their teaching. This study investigated the representation of gender in an English textbook for junior high school level: When English Rings a Bell. Halliday’s transitivity system (Halliday & Matthiessen, 2004, 2014) is applied in this qualitative study to reveal how gender is represented. The result shows female characters dominate the roles of Participants. Regarding the types of Processes, the depictions of male and female characters are both significant in Relational processes; however, female characters are more frequently represented than male characters in other Processes. It is observed that both males and females are mostly attributed with positive personality adjectives. Only a few male characters are associated with negative traits. This study is expected to provide teachers and book authors with references of gender representations in the textbook so they can be aware of the imbalance and actively contribute to lessen this discrepancy. Keywords: Textbook, gender representation, English, ideology